Hypoxia‐induced YAP activation and focal adhesion turnover to promote cell migration in mesenchymal TNBC cells - Thi My Hang Nguyen; Yi‐Shyun Lai; Ying‐Chi Chen; Tzu‐Chien Lin; Ngoc Thang Nguyen; Wen‐Tai Chiu (Cancer Medicine, 2023)
Abstract Background Hypoxia is commonly characterized by malignant tumors that promote the aggressiveness and metastatic potential of cancer. Triple‐negative breast cancer (TNBC) is the most aggressive subtype of breast cancer, with approximately 46% capacity related to distant metastasis. Transcriptional factor yes‐associated protein (YAP), a core component of the Hippo pathway, is associated with poor prognosis and outcome in cancer metastasis. Here, we explored the effect of hypoxia‐mediated YAP activation and focal adhesions (FAs) turnover in mesenchymal TNBC cell migration. Methods We characterized the effect of hypoxia on YAP in different breast cancer cell lines using a hypoxia chamber and CoCl2. Results Hypoxia‐induced YAP nuclear translocation is significantly observed in normal breast epithelial cells, non‐TNBC cells, mesenchymal TNBC cells, but not in basal‐like TNBC cells. Functionally, we demonstrated that YAP activation was required for hypoxia to promote mesenchymal TNBC cell migration. Furthermore, hypoxia induced the localization of FAs at the leading edge of mesenchymal TNBC cells. In contrast, verteporfin (VP), a YAP inhibitor, significantly reduced the migration and the recruitment of nascent FAs at the cell periphery under hypoxia conditions, which only showed in mesenchymal TNBC cells. Conclusions Our data support the hypothesis that YAP is novel factor and positively responsible for hypoxia‐promoting mesenchymal TNBC cell migration. Our findings provide further evidence and outcomes to help prevent the progression of TNBC.